X=x2-9x

Simple and best practice solution for X=x2-9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X=x2-9x equation:



X=X2-9X
We move all terms to the left:
X-(X2-9X)=0
We add all the numbers together, and all the variables
-(+X^2-9X)+X=0
We get rid of parentheses
-X^2+9X+X=0
We add all the numbers together, and all the variables
-1X^2+10X=0
a = -1; b = 10; c = 0;
Δ = b2-4ac
Δ = 102-4·(-1)·0
Δ = 100
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{100}=10$
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(10)-10}{2*-1}=\frac{-20}{-2} =+10 $
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(10)+10}{2*-1}=\frac{0}{-2} =0 $

You can always share this solution

See similar equations:

| x=9x+18 | | (u-2)=2U^2-2U-4 | | 2x+4+2x=2x+12+4x | | 12+3=12+y | | 7w-3(5+w)=10+3 | | 7+2(4x–3)=-15 | | 2x-(2+4x)=3(x+2)+1 | | 11+8x=3(-3+4x) | | -6(2x+1)=3x+7-9 | | 15=h/2-11 | | -5(z+1)-3(-1-z)=-30 | | -6(2x+1)=3x+79x | | 4.9x+4.5=19.2 | | 2x+26+6=x+23 | | 9=g/2+6 | | y-22=-42 | | -x+5/2=9 | | X+8(1-x)=1 | | 4m+9=5m-8/5 | | -36=-9(6+2x) | | 8=f/2+6 | | 54+x=-78 | | 1+2r+6=3 | | y-17=-46 | | 2r/5=3r | | 6x+10/3=5 | | 5x/3+3=8 | | 5x?1=24 | | 5/6+6(x)=7(x)-2/3 | | 6n+5-10n=4n+4-7n | | 9=6x+2+7x | | 8-7y=10 |

Equations solver categories